Influence of Pranic Agriculture on Morphological Traits, Chlorophyll Content and Genetic Polymorphism of Ridge Gourd (Luffa acutangula L. Roxb.) Assessed by RAPD Marker Analysis - Poornima, R.; Prasad, K. Nagendra; Yathindra, H. A.; Jois, Srikanth N. (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2020)
Pranic agriculture is a newly emerging concept of sustainable and eco-friendly agriculture. Pranic agriculture techniques are applied to plants before sowing and at the time of plant development to improve growth and yield. The present study aimed to understand the influence of pranic agriculture on growth, yield, and genetic polymorphism of ridge gourd. An increase in root length by 38%, stem girth by 8%, and the number of days taken for the premier harvest was advanced and found to be significant (p<.05) in pranic treated plots against the control. Chlorophyll content was 26% higher (p<.05) in pranic treated plants when compared to control. To find out the probable effects of pranic agriculture at molecular levels, RAPD marker analysis was carried out and average polymorphism up to 47% was observed between pranic and control treatments. Thus, pranic treatment was found to be very effective in increasing the overall growth and yield of ridge gourd. Further, in-depth studies are warranted about molecular mechanisms that are bringing changes in the plants after pranic treatment.